2018
DOI: 10.5935/abc.20180019
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Relationship between TSH Levels and Prognosis in Acute Coronary Syndrome?

Abstract: BackgroundSome small studies have related higher levels of thyrotropin (TSH) to potentially worse prognosis in acute coronary syndromes. However, this relationship remains uncertain.ObjectiveTo analyze the outcomes of patients with acute coronary syndromes in relation to the value of TSH at admission.MethodsObservational and retrospective study with 505 patients (446 in group I [TSH ≤ 4 mIU/L] and 59 in group II [TSH > 4 mIU/L]) with acute coronary syndromes between May 2010 and May 2014. We obtained data abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…6 Another analysis of patients with acute coronary syndrome revealed that patients with high TSH levels (>4mU/L) had poorer outcomes. 24 It is difficult to evaluate the true association of thyroid function with outcomes in these studies as TSH levels are affected by the illness as well as its treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Another analysis of patients with acute coronary syndrome revealed that patients with high TSH levels (>4mU/L) had poorer outcomes. 24 It is difficult to evaluate the true association of thyroid function with outcomes in these studies as TSH levels are affected by the illness as well as its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There were 168 mortality events over a median (IQR) follow-up period of 28 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) months: 31 (9.9%) events in patients with SCH on admission and 135 (9.2%) events in euthyroid patients. When uniform TSH reference intervals were utilized, SCH was not associated with all-cause mortality (HR, 1.06; 95%CI, 0.69 -1.62; p-value, 0.80).…”
Section: Sample Timing and Risk Of Remaining In Sctd Statementioning
confidence: 99%
“…A study done by de Matos Soeiro et al (2017) with 505patients found out that the ACS patients having TSH >4 mlU/L at admission had worse prognosis in terms of higher incidence of in-hospital combined events, cardiogenic shock and bleeding. 48 There is a strong connection of low T3 with impaired ventricular function among AMI patients which concludes that T3 levels may represent as a predictor for ventricular functional recovery, 49 Also, it has been reported that the extent of trans mural involvement in patients with STEMI assessed by cardiac magnetic resonance imaging 40 days after the event is strongly associated with T3 levels. 50 The association of the low T3 syndrome relates to worse prognosis and mortality among patients suffering from AMI and may also be an independent marker not necessarily associated only with the degree of myocardial necrosis.…”
Section: The Prognostic Value Of Thyroid Dysfunction In Acsmentioning
confidence: 99%
“…A recent study showed that TSH more than 4 is correlated with worse hospital outcomes. 38 Another recent study showed that women with high TSH were at significantly higher risk of increased mortality from coronary artery disease. 39 Most of our patients were male, and this more likely why our result was non-significant.…”
Section: Discussionmentioning
confidence: 99%